Elementary School Teachers' Experiences in Implementing Inclusive Learning Processes - Rizka Khaulah Asysyaffa; Muhammad Fauzan Muttaqin (Penerbit Presisi Pustaka, 2026)
Inclusive education is an educational approach that provides opportunities for all students, including children with special needs, to learn together within the same educational setting. The implementation of inclusive education in elementary schools requires teachers not only to master instructional content but also to possess understanding, skills, and attitudes that support the diversity of students’ characteristics. This study aims to describe elementary school teachers’ experiences in implementing inclusive learning, including planning, implementation, and challenges encountered during the learning process. The study employed a qualitative approach with teachers from an inclusive elementary school, SDN Patramanggala 02, as research subjects. Data were collected through in-depth interviews, observations, and documentation to obtain a comprehensive overview of inclusive learning practices. The results indicate that teachers have diverse experiences in managing inclusive classrooms, such as adapting learning strategies and methods, managing classes with heterogeneous student characteristics, and facing limitations in facilities and the lack of specialized training related to inclusive education. Nevertheless, teachers strive to create a friendly and inclusive learning environment through individualized approaches, collaboration with the school, and the development of creativity in teaching. In conclusion, the success of inclusive learning is strongly influenced by teachers’ readiness and active roles, as well as the support of school facilities and policies in realizing inclusive and equitable education for all students.